Interaction design beyond human-computer interaction - Sharp, Helen; Rogers, Yvonne; Preece, Jenny (John Wiley and Sons, 2019)
"Interaction design is about designing interactive digital products to support the way people communicate and interact in their everyday and working lives. To be successful, interaction designers need a mixed set of skills drawn from human–computer interaction, web design, psychology, computer science, information systems, data science and the human sciences as well as an understanding of the desires and needs of people and the kinds of technology available. Interaction Design: beyond human–computer interaction offers a cross-disciplinary, practical and process-oriented introduction to the field, showing not just what principles ought to apply to interaction design, but crucially how they can be applied. The fifth edition of this best-selling book has been substantially updated to reflect this dynamic and fast-moving field and includes: A new chapter – Data at Scale Application of contemporary theory about human cognition to Interaction Design New developments in social and emotional interaction The latest on Agile and LeanUX Extensive coverage of UX design and evaluation methods Commentary on new and traditional interfaces and applications Updated interviews with leaders in the field from consultancy, corporations and academia Interaction Design??is hugely popular with students and professionals alike. It is an ideal resource for learning the interdisciplinary skills needed for interaction design human–computer interaction, information design, web design, and how HCI relates to topical issues in AI and data science. Accompanying the text is an extensive website at http://www.id-book.com which contains additional teaching and learning material. It also contains over 50 talking-head videos with HCI experts answering questions like 'what is the future of HCI?'"--